Web 3.0 - the semantic web: high-impact strategies - what you need to know: definitions, adoptions, impact, benefits, maturity, vendors - Roebuck, Kevin (CPSIA, 2011)
The Semantic Web is a ´´web of data´´ that facilitates machines to understand the semantics, or meaning, of information on the World Wide Web. It extends the network of hyperlinked human-readable web pages by inserting machine-readable metadata about pages and how they are related to each other, enabling automated agents to access the Web more intelligently and perform tasks on behalf of users. The term was coined by Tim Berners-Lee, the inventor of the World Wide Web and director of the World Wide Web Consortium ("W3C"), which oversees the development of proposed Semantic Web standards. He defines the Semantic Web as "a web of data that can be processed directly and indirectly by machines." This book explains in-depth the real drivers and workings of Web 3.0. It reduces the risk of your technology, time and resources investment decisions by enabling you to compare your understanding of Web 3.0 with the objectivity of experienced professionals